On the Source Parameters and Genesis of the 2017, Mw 4 Montesano Earthquake in the Outer Border of the Val d’Agri Oilfield (Italy) - López-Comino, José Ángel; Braun, Thomas; Dahm, Torsten; Cesca, Simone; Danesi, Stefania (Frontiers in Earth Science, 2021)
On October 27th, 2017, a Mw 4 earthquake occurred close to the municipality of Montesano sulla Marcellana, less than 10 km external to the concession of the largest European on-shore hydrocarbon reservoir - the Val d’Agri oilfield (Southern Italy). Being a weak event located outside the extended monitoring domain of the industrial concession, the relevance of this earthquake and possible links with the hydrocarbon exploitation were not deepened. Actually, the analysis of shallow seismic events close to subsurface exploitation domains plays a significant role for the definition of key parameters in order to discriminate between natural, triggered and induced seismicity, especially in tectonically active regions. The study of weak to moderate earthquakes can improve the characterization of the potentially destructive seismic hazard of this particular area, already struck by M>6.5 episodes in the past. In this work, we analyze the source parameters of this Mw 4 earthquake applying advanced seismological techniques to estimate the uncertainties derived from the moment tensor inversion and identify plausible directivity effects. The moment tensor is dominated by a NW-SE oriented normal faulting with a centroid depth of 14 km. A single ML 2.1 aftershock was recorded and used as empirical Green function to calculate the apparent source time function for the mainshock. Apparent durations (in the range 0.11 - 0.21 s, obtained from S-waves) define an azimuthal pattern which reveals an asymmetric bilateral rupture with the 70% of the rupture propagation in the N310°W direction, suggesting a rupture plane dipping to the SW. Our results tally with the activation of a deeper fault segment associated to the Eastern Agri Fault System close to the basement as the origin for the Montesano earthquake. Finally, the Coulomb stress rate induced by depletion of the oilfield is calculated to quantify the trigger potential estimated for the Montesano earthquake yielding relatively low probabilities below 10%. Our analyses point toward the conclusion that the Mw 4 event was more likely due to the local natural tectonic stress, rather than induced or triggered by the long-term hydrocarbon extraction in the Val d’Agri oilfield.